Western texts and new worlds politics of identity in a Philippine fan community - Santos, Maria Lorena M. (Philippine Humanities Review:Rebyu ng Arte at Literatura ng Pilipinas, 2013)
Media scholar John Fiske asserts that fandom is "associated with the cultural tastes of subordinated formations of the people, particularly with those disempowered by any combination of gender, age, class and race." American cultural theorists have sought to rescue marginalized fans from stereotypes as passive consumers, deviants, and social misfits by representing them as active appropriators and transformers of texts. In the Philippines, however, some fan communities need no rescuing as they are associated not with subordination and social ineptitude but with high cultural and economic capital. This paper uses a cultural studies approach to read the cultural practices of the New Worlds Alliance (NWA), a Philippine science fiction and fatasy fan community whose objects of veneration include such print and media texts as the Harry Potter series, The Lord of the Rings, Star Wars, and Star Trek. I argue that the NWA's member composition, its (Western) objects of fandom, its activities and fan products, and its self-representation (i.e., the celebratory construction of the Philippine "geek") highlight the disparities between center and periphery, rich and poor, and local and global in the Philippines. Given the community's privileged class position in the Philippine context, the politics of its identity-construction cannot be adequately explained by fan theories that have been applied to American audiences. Thus, I seek to examine the NWAs discourses of empowerment and cultural superiority in order to critique American models of "geekdom" as exemplifying weapons of the weak or of fandom as liberatory cultural practice.